White Blood Cell Counts, Alcoholism, and Cirrhosis in Pneumococcal Pneumonia. (24th February 2017) - Gardner, Julianna G.; Bhamidipati, Divya R.; Rueda, Adriana M.; Nguyen, Duc T. M.; Graviss, Edward A.; Musher, Daniel M.
Abstract: Background: An elevated white blood cell (WBC) count is a characteristic finding in pneumococcal pneumonia. Very low WBC counts, occurring in some cases, are often associated with overwhelming pneumonia and have been attributed to alcohol-induced suppression of bone marrow. However, a systematic study of neutropenia, leukocytosis, alcohol ingestion, and cirrhosis in pneumococcal pneumonia has not been previously reported. Methods: Using a database of patients with pneumococcal pneumonia at our medical center, we extracted data on WBC counts at admission, differential counts, alcohol ingestion, and cirrhosis, and we related these to 7-day and 30-day mortality. Results: White blood cell counts were <6000/mm 3 in 49 of 481 patients (10.2%) with pneumococcal pneumonia and >25000/mm 3 in 40 (8.3%). Mortality at 7 days was 18.4% and 12.5%, respectively, 5-fold and 3-fold greater in patients with WBC <6000 or >25000 than in those with WBC counts between 6000 and 25000 ( P < .001). Increased band forms were not associated with a worse outcome ( P = .12). Alcohol use and cirrhosis were not associated with WBC counts <6000 ( P = .63 and P = .41, respectively). Conclusions: In a large series of cases of pneumococcal pneumonia, WBC counts <6000 or >25000 correlated significantly with increased 7-day mortality. More than 10% band forms was not associated with a poor outcome. Alcohol abuse was not associated with low WBC or increased mortality. Our findings suggest that greater consideration be given to more intense care for patients with bacterial pneumonia who have very high or very low WBC counts at the time of hospital admission.